Determinants of Student's Intention to Online Cash Waqf Using Modification of Technology Acceptance Model - A'yun Qolbi; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Tujuan dari Penelitian ini adalah menguji pengaruh kepercayaan dan citra website yang diintegrasikan dengan persepsi kemudahan penggunaan dan persepsi kebermanfaatan pada niatan seorang mahasiswa dalam membayar wakaf secara online, yang menjadikan penelitian ini berbeda dengan penelitian sebelumnya adalah penggunaan citra website sebagai determinan niatan mahasiswa dalam menggunakan layanan wakaf online ini. Penelitian ini menggunakan pendekatan kuantitatif dengan metode SEM-PLS serta melibatkan responden sebesar 100 responden dengan menggunakan Purposive Sampling dengan kriteria seorang muslim usia 18-35 dan seorang mahasiswa. Software analisis untuk mengolah data dalam penelitian ini menggunakan Smartpls 3.3, untuk data diperoleh dengan menggunakan kuesioner online menggunakan skala likert 1 sampai 5, dengan keterangan sangat setuju hingga tidak setuju. Hasil dari penelitian ini menunjukkan bahwa kepercayaan, citra website, kebermanfaatan aplikasi, dan kemudahan penggunaan berhubungan signifikan terhadap niat penggunaan wakaf online. Implikasi hasil penelitian ini diharapkan dapat memberikan tambahan pengetahuan terutama dalam ilmu pemasaran Islam terkait penggunaan behavioral intention dalam penggunaan layanan wakaf online, serta diharapkan penelitian ini dapat memberikan masukan bagi manajemen lembaga donasi terutama nazir untuk lebih memperhatikan kemudahan penggunaan konsumen, manfaat yang dirasakan, kepercayaan lembaga, citra perusahaan serta niat dalam menggunakan layanan wakaf secara online. Kata kunci: Wakaf online, technology acceptance model, trust, image.   ABSTRACT The purpose of this study was to examine the effect of trust and website image, which is integrated with perceived ease of use and perceived usefulness, on a student's intention to pay waqf online. What makes this research different from previous research is using website images to determine student intention in using this online waqf service. This study uses a quantitative approach with the SEM-PLS method and involves 100 respondents using purposive sampling with the criteria of a Muslim aged 18-35 and a student. The analysis software to process data in this study used Smartpls 3.3 for data obtained using an online questionnaire using a Likert scale of 1 to 5, with statements strongly agreeing to disagree. This study indicates that trust, website image, application usefulness, and ease of use are significantly related to the intention to use online waqf. The implications of the results of this study are expected to provide additional knowledge, especially in Islamic marketing related to the use of behavioral intention in the use of online waqf services. It is hoped that this research can provide input for the management of donation institutions, especially Nazir, to pay more attention to consumers' ease of use, perceived benefits, and institutional trust., corporate image and intention to use online waqf services. Keywords: online waqf, technology acceptance model, trust, image.   DAFTAR PUSTAKA Abdul Shukor, S., Johari, F., Abd Wahab, K., Kefeli Zulkefli, Z., Ahmad, N., Haji Alias, M., Abdul Rahman, A., Mohd Orip, N. M., Ibrahim, P., & Abu-Hussin, M. F. (2019). Trust on awqaf institutions: evidence from Malaysia. Journal of Islamic Marketing, 10(2), 511–524. https://doi.org/10.1108/JIMA-05-2017-0054 Ahn, J. chang, Sura, S., & An, J. C. (2018). Intention to donate via social network sites (SNSs): A comparison study between Malaysian and South Korean users. Information Technology and People, 31(4), 910–926. https://doi.org/10.1108/ITP-12-2015-0307 Aldeen, K. N., Ratih, I. S., & Herianingrum, S. (2020). Contemporary issues on cash waqf: A thematic literature review. International Journal of Islamic Economics and Finance (IJIEF), 3(3), 119–144. https://doi.org/10.18196/ijief.3236 Alrubaiee, L. S., Aladwan, S., Abu Joma, M. H., Idris, W. M., & Khater, S. (2017). Relationship between corporate social responsibility and marketing performance: The mediating effect of customer value and corporate image. International Business Research, 10(2), 104. https://doi.org/10.5539/ibr.v10n2p104 Bailey, A. A., Pentina, I., Mishra, A. S., & Ben Mimoun, M. S. (2017). Mobile payments adoption by US consumers: An extended TAM. International Journal of Retail and Distribution Management, 45(6), 626–640. https://doi.org/10.1108/IJRDM-08-2016-0144 Berakon, I., Aji, H. M., & Hafizi, M. R. (2021). Impact of digital sharia banking systems on cash-waqf among Indonesian Muslim youth. Journal of Islamic Marketing. https://doi.org/10.1108/JIMA-11-2020-0337 Blagoeva, K. T., & Mijoska, M. (2017). Applying TAM to study online shopping adoption among youth in the republic of Macedonia. Genetika, 46(3), 27–32. Eneizan, B., Alsaad, A., Alkhawaldeh, A., Rawash, H. N., & Enaizan, O. (2020). E-WOM, trust, usefulness, ease of use, and online shopping via websites: The moderating role of online shopping experience. Journal of Theoretical and Applied Information Technology, 98(13), 2554–2565. Faisal, M., Yusof, M., Alam, S., Faiz, M., Yusof, M., Alam, S., Hasarudin, M. H., Alam, S., Romli, N., Lumpur, K., Terms, G., & Statement, P. (2014). Cash waqf and infaq: A proposed e-philanthropy in Malaysia. Jurnal Kemanusiaan, 12(1), 1–10. Hair Jr., J. F., Gabriel, M. L. D. da S., & Patel, V. K. (2014). Modelagem de equações estruturais baseada em covariância (CB-SEM) com o AMOS: Orientações sobre a sua aplicação como uma Ferramenta de Pesquisa de Marketing. Revista Brasileira de Marketing, 13(2), 44–55. https://doi.org/10.5585/remark.v13i2.2718 Indahsari, K., Burhan, M. U., Ashar, K., & Multifiah. (2014). Determinants of individual Muslim behaviour in accomplishing zakah, infaq, shadaqah and waqf through amil institution. International Journal of Economic Policy in Emerging Economies, 7(4), 346–365. https://doi.org/10.1504/IJEPEE.2014.066627 Iskandar, M., Hartoyo, H., & Hermadi, I. (2020). Analysis of factors affecting behavioral intention and use of behavioral of mobile banking using unified theory of acceptance and use of technology 2 model approach. International Review of Management and Marketing, 10(2), 41–49. https://doi.org/10.32479/irmm.9292 Joseph, S. (2014). Waqf in historical perspective: Online fatāwā and contemporary discourses by muslim scholars. Journal of Muslim Minority Affairs, 34(4), 425–437. https://doi.org/10.1080/13602004.2014.965974 Kasri, R. A., & Chaerunnisa, S. R. (2021). The role of knowledge, trust, and religiosity in explaining the online cash waqf amongst Muslim millennials. Journal of Islamic Marketing. https://doi.org/10.1108/JIMA-04-2020-0101 Klopping, I. M., & Mckinney, E. (2004). Extending the technology acceptance model and the task-technology fit model  to consumer e-commerce. Information Technology, Learning, and Performance Journal, 22(1), 35–48. Lubis, H. (2020). Potensi dan strategi pengembangan wakaf uang di indonesia. IBF: Islamic Business and Finance, 1(1), 43–59. Masrikhan, M. (2019). Optimalisasi potensi wakaf di era digital melalui platform online wakafin.com dengan konsep crowdfunding sebagai penggerak ekonomi masyarakat. Jurnal Ekonomi Syariah, 1, 1–12. Mohd Thas Thaker, M. A. Bin. (2018). Factors influencing the adoption of the crowdfunding-waqf model (CWM) in the waqf land development. Journal of Islamic Marketing, 9(3), 578–597. https://doi.org/10.1108/JIMA-05-2016-0043 Mohd Thas Thaker, M. A., Mohd Thas Thaker, H., A.Pitchay, A., & Khaliq, A. (2019). A proposed integrated zakat-crowdfunding model (IZCM) for effective collection and distribution of zakat fund in Malaysia. International Journal of Zakat and Islamic Philanthropy, 1(2), 1–12. Niswah, F. M., Mutmainah, L., & Legowati, D. A. (2019). Muslim millennial’s intention of donating for charity using fintech platform. Journal of Islamic Monetary Economics and Finance, 5(3), 623–644. https://doi.org/10.21098/jimf.v5i3.1080 Nour Aldeen, K., Ratih, I. S., & Sari Pertiwi, R. (2021). Cash waqf from the millennials’ perspective: a case of Indonesia. ISRA International Journal of Islamic Finance, ahead-of-p(ahead-of-print). https://doi.org/10.1108/ijif-10-2020-0223 Phatthana, W., & Mat, N. K. N. (2011). The application of technology acceptance model (TAM) on health tourism e-purchase intention predictors in Thailand. 2010 International Conference on Business and Economics Research, 1, 196–199. http://www.ipedr.com/vol1/43-B10046.pdf Raza, S. A., Shah, N., & Ali, M. (2019). Acceptance of mobile banking in Islamic banks: Evidence from modified UTAUT model. Journal of Islamic Marketing, 10(1), 357–376. https://doi.org/10.1108/JIMA-04-2017-0038 Rybaczewska, M., Sparks, L., & Sułkowski, Ł. (2020). Consumers’ purchase decisions and employer image. Journal of Retailing and Consumer Services, 55(October 2019), 0–7. https://doi.org/10.1016/j.jretconser.2020.102123 Sabri, F. A. (2014). Wakaf uang (Sebuah alternatif dalam upaya menyejahterakan masyarakat). AL-IHKAM: Jurnal Hukum & Pranata Sosial, 8(1), 40–54. https://doi.org/10.19105/al-lhkam.v8i1.339 Shaikh, I. M., Qureshi, M. A., Noordin, K., Shaikh, J. M., Khan, A., & Shahbaz, M. S. (2020). Acceptance of Islamic financial technology (FinTech) banking services by Malaysian users: An extension of technology acceptance model. Foresight, 22(3), 367–383. https://doi.org/10.1108/FS-12-2019-0105 Singh, S., Sahni, M. M., & Kovid, R. K. (2020). What drives fintech adoption? A multi-method evaluation using an adapted technology acceptance model. Management Decision, 58(8), 1675–1697. https://doi.org/10.1108/MD-09-2019-1318 Sohn, S. (2017). A contextual perspective on consumers’ perceived usefulness: The case of mobile online shopping. Journal of Retailing and Consumer Services, 38(May), 22–33. https://doi.org/10.1016/j.jretconser.2017.05.002 Usman, H., Mulia, D., Chairy, C., & Widowati, N. (2020). Integrating trust, religiosity and image into technology acceptance model: the case of the Islamic philanthropy in Indonesia. Journal of Islamic Marketing. https://doi.org/10.1108/JIMA-01-2020-0020 Victoria, O. A., Pujirahayu, E. W., Khisni, A., & Ong, R. (2019). Law development of waqf al-nuqud (Cash waqf) towards electronic waqf (E-waqf) based on public welfare. LDJ: Law Development Journal, 1(1), 13–17. Wadi, D. A., & Nurzaman, M. S. (2020). Millennials behaviour towards digital waqf innovation. International Journal of Islamic Economics and Finance (IJIEF), 3(3), 1–30. https://doi.org/10.18196/ijief.3232 Wong, K. K. K.-K. (2013). Partial least squares structural equation modeling (PLS-SEM) techniques using SmartPLS. Marketing Bulletin, 24(1), 1–32. Retrieved from http://marketing-bulletin.massey.ac.nz/v24/mb_v24_t1_wong.pdf%5Cnhttp://www.researchgate.net/profile/Ken_Wong10/publication/268449353_Partial_Least_Squares_Structural_Equation_Modeling_(PLS-SEM)_Techniques_Using_SmartPLS/links/54773b1b0cf293e2da25e3f3.pdf Zhang, E. M. (2010). Understanding the acceptance of mobile SMS advertising among young chinese consumers. Psychology & Marketing, 30(6), 461–469. https://doi.org/10.1002/mar